(untitled) (Journal of Pharmaceutical Negative Results, 2022)
According to various scientific experiments, many language learners have difficulties in learning pronunciation, they have problems explaining their speech to others while speaking English, and they have problems in understanding others' speech. To eliminate and prevent these, we must use effective methods and tools in teaching pronunciation. The role of technical means is incomparable in this. Technical means can be understood as phonograms, videos, audio-video programs and television, video device, computer, as well as projector, dictaphone and many other language teaching tools that allow their use. These tools can be used independently and in the classroom. Since English language is needed for personnel in all fields, it is becoming important to teach the language at the level of modern requirements and using technologies. While learning English, we should master it fluently and without various mistakes, especially without pronunciation defects. The reason is that language is a communicative tool, and if we make typical mistakes in its use, it can lead to misunderstandings between the speaker and the interlocutor. If the speaker does not have the skills of correct pronunciation, his careful mastery of words and grammar seems insignificant and he cannot show his knowledge and skills to everyone.